, DMCN 43: 234–8 (Developmental Medicine and Child Neurology, 2001)
Aim To investigate the efficacy of the Hand-Arm Bimanual Intensive Therapy Including Lower Extremities (HABIT-ILE) compared with usual physiotherapy delivered at the same dosage in children with bilateral cerebral palsy (CP) in Benin. Method This randomized controlled trial involved 32 children (19 males, 13 females) with bilateral CP, aged 2 to 4 years, classified in Gross Motor Function Classification System levels III and IV, randomly allocated to HABIT-ILE or a high-dosage physiotherapy group. Interventions were delivered at a 2-week camp. Children were assessed before and after interventions and at the 2-month follow-up using the Gross Motor Function Measure (GMFM), the Both Hands Assessment (BoHA), the Canadian Occupational Performance Measure (COPM), and the Activity Limitations Questionnaire, West African version (ACTIVLIM-CP-WA). Results A significant group × testing time interaction indicated a significant improvement in GMFM scores after HABIT-ILE, which was sustained at the follow-up. Children in the usual physiotherapy group improved slightly at the follow-up. No significant changes in BoHA were observed in either group. Both groups improved in COPM scores, with a larger improvement after HABIT-ILE. The ACTIVLIM-CP-WA measures improved over time with no group differences. Interpretation HABIT-ILE is more efficacious in improving motor and functional outcomes in children with bilateral CP than usual physiotherapy administered at the same dosage, demonstrating the importance of therapy content.